2001
DOI: 10.1017/s1481803500005819
|View full text |Cite
|
Sign up to set email alerts
|

Is propofol an optimal agent for procedural sedation and rapid sequence intubation in the emergency department?

Abstract: Objective:We conducted a qualitative systematic review to evaluate the efficacy and safety of propofol for direct current cardioversion (DCC), rapid sequence intubation (RSI) and procedural sedation in adult emergency department (ED) patients. Data source: MEDLINE (1966 to September 2000, PubMed (to September 2000), EMBASE (1988 to September 2000, Database of Systematic Reviews (to September 2000), Best Evidence (1991 to September 2000) and Current Contents (1996 to September 2000) databases. Study selection:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
0
20
0
1
Order By: Relevance
“…23,24 Toward improving patient safety, this study was designed to determine whether administration of the AMPAKINE CX717 would offer protection against propofol-induced respiratory depression. The hypothesis is based on the fact that CX717 increases the strength and efficacy of glutamatergic neurotransmission via AMPARs that is essential for controlling neuronal excitability in key respiratory neuronal populations.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Toward improving patient safety, this study was designed to determine whether administration of the AMPAKINE CX717 would offer protection against propofol-induced respiratory depression. The hypothesis is based on the fact that CX717 increases the strength and efficacy of glutamatergic neurotransmission via AMPARs that is essential for controlling neuronal excitability in key respiratory neuronal populations.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol has been used for procedural sedation in Emergency Medicine since 1995 7. In 1996, in a review article in Anaesthesia ,8 it was recommended as the drug which most closely approaches the ideal agent for cardioversion; however, a systematic review of the use of propofol for procedural sedation in Emergency Medicine in 2001 concluded that although there was evidence to support the use of propofol for DCCV this evidence came from stable patients in a non-ED setting, and there was as yet no evidence to support its use in emergency practice 9. Since then, Miner et al 10 have shown that procedural sedation in the ED with propofol appears to be safe in ASA class III and IV patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the parameters evaluated in the present study, we can conclude Propofol as a superior sedating agent compared to Diazepam, having rapid onset and predictability of action, profoundness of amnesia and a faster recovery period, offering advantages of early patient discharge and better patient compliance [28].…”
Section: Resultsmentioning
confidence: 73%